New species of freshwater bryozoans Plumatella sibirica (Phylactolaemata), Western Siberia (Russia) - Gontar V. I.; Sharapova T. A. (Vestnik MGTU, 2023)
Western Siberia is the least studied region with respect to the distribution, ecology, and systematic composition of freshwater bryozoans. The collection of material on freshwater bryozoans of the West Siberian Plain was carried out as part of study of the zooperiphyton of the water bodies of the Tyumen region (including the Khanty-Mansiysk and Yamalo-Nenets Autonomous Districts) in 1987–2016. As a result of the collected material analysis, description of a new species of phylactolemic bryozoans (Bryozoa) Plumatella sibirica has been presented. The new species has autozooids in the form of tubules with a rounded cross section. Phlotoblasts are oval, with slightly narrowed poles. Size and surface morphology of flotoblasts and sessoblasts distinguish the species from related species Plumatella repens (Linné) and P. buschnelli (Wood). The maximum biomass of zooperiphyton in forest-tundra lakes has been noted in communities dominated by large colonies of Plumatella sibirica, where this bryozoan is the absolute dominant. In the course of further studies, a new species of bryozoans Plumatella sibirica may also be found in other regions of Siberia.